(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Basri NIA, Zakaria N. 2021. Butterfly communities (Insecta: Lepidoptera) at two recreational areas in Sungai Petani, Kedah, Peninsular Malaysia. Biodiversitas 22: 5039-5047. The knowledge on the butterfly diversity, especially in various habitats in Kedah is still poor. A study was conducted to determine and compare the diversity of butterflies at two recreational areas in Sungai Petani, Kedah, namely Bukit H and Taman Jubli Perak. This study was carried out starting from January 2021 until March 2021 with a total of nine sampling occasions at each site. Visual Encounter Survey (VES) was chosen as a sampling method. The butterflies were captured using a sweep net from 9am to 11am and 12pm to 2pm for each sampling site. A total of 145 individuals from 13 species from four families of butterflies were recorded. The most abundant species were recorded from the family Nymphalidae. Chilades pandava was the most abundant species obtained from the two recreational areas. From the t-test analysis, there was no significant difference between the diversity of Bukit H and Taman Jubli Perak. Shannon and Simpson’s diversity indices showed both sites were interpreted as moderately low in diversity. This may be due to the different types of vegetation that exist at both sampling sites. This study will contribute to the first record of butterflies in Sungai Petani, Kedah, Peninsular Malaysia.